Representation of Independence in Guru Aini's Novel and Its Implications for Literacy Practices in Schools - Sulami, Sri; Widayati, Mukti; Nurnaningsih, Nurnaningsih (Universitas Cokroaminoto Palopo, 2025)
Independence is a crucial character trait that needs to be developed in educational settings. This study aims to analyze the representation of independence in Andrea Hirata's novel Guru Aini and examine its practical implications for literacy practices in schools, specifically focusing on students' behavioral and psychological conditions regarding literacy habits. This qualitative descriptive study employed a case study approach based on literary psychology perspective. Data consisted of words, statements, quotations, and sentences containing independence meanings from the 200-page novel Guru Aini published by Pustaka Belitung. Data collection utilized analytical reading and note-taking techniques. Data validity was ensured through source and method triangulation. Content analysis with literary psychology approach was employed, followed by interactive data analysis including data collection, reduction, presentation, and conclusion drawing. The study identified three forms of independence representation: (1) Emotional independence - characters' ability to manage feelings without external support; (2) Social independence - adaptation and interaction capabilities in diverse environments; (3) Professional independence - autonomous decision-making in academic and career pursuits. The analysis revealed that literacy habits focusing on independence support students' development of critical thinking, autonomous learning, and responsibility. Literary works can serve as effective media for instilling independence values in students. The implications suggest that incorporating independence-themed literature in school literacy programs can enhance students' character development and learning autonomy.